Analisis Kadar Glial Fibrillary Acidic Protein dengan Tingkat Keparahan Cedera Kepala di Rumah Sakit Umum Pusat (RSUP) Haji Adam Malik - Sinulingga, R. Disfahan Yonanda; Japardi, Iskandar; Sastrodiningrat, Abdul Gofar (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction This study was to determine the relationship of serum Glial Fibrillary Acidic Protein (GFAP) levels with severity of head injury patients.Methods This study was an analytical study using cross-sectional design. The study lasted from June 2013 until March 2014 at Adam Malik General Hospital. Severe head injury patients were included in the study if the onset is less than 48 hours. Selected patients were evaluated based on the findings of the Computed Tomography (CT) scan of the head. Consecutive sampling was done to select the subjects, then blood samples were taken for examination and imeasurement of cumulative GFAP serum level.Results The results showed that GFAP levels were associated significantly with GCS after resuscitation (r = -0.631, p = 0.0001). The correlation was a negative correlation (r = -0.631, p = 0.0001). If the higher Glasgow Coma Scale (GCS) after resuscitation, serum GFAP levels would be even lower.Conclusion Levels of GFAP severe head injury patients (11.9 Â± 10.52) was significantly higher compared to patients with moderate head injury (1.82 Â± 1.60, p = 0.0001). There is a significant correlation between serum GFAP levels with initial GCS after resuscitation (r = -0.631, p = 0.0001).Keywords : GFAP, head injury, biomarker